Diabetic pregnancy, maternal and fetal docosahexaenoic acid: a review of existing evidence. (19th May 2018) - Léveillé, Pauline; Rouxel, Clémence; Plourde, Mélanie
Abstract: Objective: Docosahexaenoic acid (DHA) is vital for fetal development especially during the third trimester of gestation when the speed of fetal brain growth is at its peak. Diabetes modifies the maternal fatty acid profile, which may in turn change the quantity and/or quality of lipids transferred to the fetus. Neonates born to diabetic mothers might be more vulnerable to DHA deficiency leading to lower cognitive scores together with lower overall intellectual quotients when compared to control. We reviewed the influence of type 1 or type 2 pre-gestational (PGD) and gestational diabetes mellitus (GDM) on maternal and fetal DHA levels. Method: We searched MEDLINE articles about PGD and/or GDM and DHA published before October 2016. Results: Maternal blood DHA level seems higher in those with diabetes than those without diabetes. However, DHA in cord plasma of neonates born to PGD and/or GDM mothers seem lower compared to neonates born to nondiabetic mothers. Conclusions: Altogether, these results suggest that the transfer of DHA from the mother to the fetus may be deficient or dysregulated in diabetic pregnancies. What remains to be understood is how placental lipid transport is regulated and whether there is a link with clinical neurodevelopmental phenotypes in the newborns.